Outcomes of ablation in Wolff-Parkinson-White-syndrome: Data from the German Ablation Registry. (15th January 2021) - Brado, Johannes; Hochadel, Matthias; Senges, Jochen; Kuck, Karl-Heinz; Andresen, Dietrich; Willems, Stephan; Straube, Florian; Deneke, Thomas; Eckardt, Lars; Brachmann, Johannes; Kääb, Stefan; Sinner, Moritz F.
Abstract: Aims: Catheter ablation is recommended for symptomatic WPW-syndrome. Commonly perceived low recurrence rates were challenged recently. We sought to identify patient strata at increased risk. Method: Of 12, 566 patients enrolled at 52 German Ablation Registry sites from 2007 to 2010, 789 were treated for WPW-syndrome. Patients were included for symptomatic palpitations and tachycardia documentation. Follow-up duration was one year. Overall complications were defined as serious, access-related, and ablation-related. We adjudicated WPW-recurrence for re-ablation during follow-up. Risk strata included: admission for repeat ablation at registry entry; accessory pathway localization; antiarrhythmic medical treatment before the ablation. Results: WPW-syndrome patients were 42.8 ± 16.2 years on average; 39.9% were women. A majority of 95.9% was symptomatic; in 84.4%, a tachycardia was documented. Seventy-six (9.6%) patients presented for repeat procedures. Accessory pathways were located in the left atrium (71.4%), right atrium (21.1%), septum (4.4%), or coronary sinus diverticula (2.1%). Prior antiarrhythmic medication was used in 43.7% of patients. No serious events occurred. The overall complication rate was 2.5% (ablation related 1.2%, access-related 1.3%). Major determinants for complications were presentation for re-ablation as registry index procedure (6.9% vs 2.2%; p  = 0.016) and septal pathway location (left 2.0% vs septal 9.1%, p  = 0.014). The overall re-ablation rate was 9.7%. Usage of prior antiarrhythmic medication was associated with higher recurrence rates (12.2% vs. 7.6%; p  = 0.035). Conclusions: Patients at higher complication risk may be identified by repeat procedure and septal pathway location. Prior antiarrhythmic medication was associated with higher recurrence rates. Our findings may help improving peri-procedural patient management and information. Highlights: We report on one of the largest recent registries for outcomes of catheter ablation in WPW-syndrome. Admission for re-ablation at of registry entry and septal pathway location were associated with higher complication rates. Antiarrhythmic treatment prior to the ablation was associated with higher re-ablation rates.